2021
DOI: 10.1002/est2.254
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study on effects of heat transfer fluids, copper mesh in packed bed and porosity, on charging time of paraffin based packed bed thermal energy storage

Abstract: In this study, a novel configuration of the latent heat thermal energy storage module based on the packed bed of encapsulated phase change material is investigated. The module is modeled and simulated using a Multiphysics tool COMSOL. The simulation results are validated with the experimental data. Using the validated model, initially, water was used as heat transfer fluid, and then refrigerant R‐134 and R‐22 were also used as heat transfer fluid (HTF) to predict the impact on the charging time. The comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…In fact, using the smaller encapsulation is one method to decrease the void fraction of packed bed system. In the similar study, Rabbi and Asif 29 numerically investigated the effects of porosity on the charging time; it was found that by reducing the porosity, charging and discharging time was reduced. Many researchers have reduced the porosity by introducing sensible heat storage medium into voids of the packed bed.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, using the smaller encapsulation is one method to decrease the void fraction of packed bed system. In the similar study, Rabbi and Asif 29 numerically investigated the effects of porosity on the charging time; it was found that by reducing the porosity, charging and discharging time was reduced. Many researchers have reduced the porosity by introducing sensible heat storage medium into voids of the packed bed.…”
Section: Introductionmentioning
confidence: 99%
“…Porous media in PCMs improves the temperature field's uniformity and reduces the PCM's melting time. Rabbi and Asif [10] studied numerically a configuration of the LHTES module based on the packed bed of encapsulated PCM integrated with copper mesh as porous media. The results indicated that when the water was used as HTF, it took 11 hours to completely charge the system.…”
Section: Introductionmentioning
confidence: 99%